Clinical Characteristics of COVID-19 Patients Infected by the Omicron Variant of SARS-CoV-2 - Zhang, Jianguo; Chen, Nan; Zhao, Daguo; Zhang, Jinhui; Hu, Zhenkui; Tao, Zhimin (Frontiers in Medicine, 2022)
Background: Currently, as the omicron variant of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) surges amid the coronavirus disease 2019 (COVID-19) pandemic, its clinical characteristics with intrinsic severity and the protection from vaccination have been understudied. Methods: We reported 169 COVID-19 patients that were infected with the omicron variant of SARS-CoV-2 and hospitalized at Suzhou, China from February to March 2022, with their demographic information, medical/immunization history, clinical symptom, and hematological profile. At the same time, patients with none/partial (one-dose), full (two-dose) and three-dose vaccination were also compared to assess the vaccine effectiveness. Findings: For the omicron COVID-19 patients included in this study, their median age was 33.0 (IQR: 24.0-45.5), 53.3% was male and the median duration from illness onset to hospitalization was 2 days. Hypertension, bronchitis, and diabetes were the leading comorbidities among patients. While common clinical symptoms included cough, fever, expectoration, and fatigue, etc., asymptomatic patients took up a significant portion (46.7%). For hematological parameters, most values revealed the alleviated pathogenicity induced by omicron variant infection. No critically ill or deceased patients due to COVID-19 infection was reported in this study. Interpretation: Our results supported that the viremic effect of omicron variant became milder than previous circulating variants, while full vaccination or booster shot was greatly desired for an effective protection against clinical severity.